A STRATEGIC LINGUOCULTUROLOGICAL MODEL FOR TEACHING ONOMASTIC UNITS IN ENGLISH AND UZBEK LANGUAGE EDUCATION - Mamatkulova Bakhtijon Ravshanovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  develops  a  strategic  linguoculturological  model  for teaching  onomastic  units  in  English  and  Uzbek  language  education.  It  argues  that proper  names  function  as  culturally  embedded  linguistic  units  that  reflect  national identity, historical memory, and social values. The study integrates strategic teaching principles with linguoculturological analysis to design an effective instructional model. The proposed model combines comparative, cognitive, and communicative strategies to facilitate deeper comprehension of onomastic meanings. The findings demonstrate that a strategically structured approach to onomastics significantly enhances learners’ intercultural communicative competence, analytical thinking, and pragmatic language use.